A new approach towards blood sugar monitoring : non-invasive/continuous/arterial - Yeo, Joon Hock. (2008)
It has been overwhelming clear that frequent monitoring and tight control of blood glucose levels are necessary for effective management of diabetic mellitus and reduction of complication associated with this disease. The current "finger prick" method is invasive, painful and troublesome for day-to-day monitoring of blood glucose. And therefore patients have tendency to give it a miss. Hence the need for a non-invasive monitoring system for blood glucose.